ANALISIS STRATA NORMA PADA PUISI SAPARDI DJOKO DAMONO BERJUDUL “ PADA SUATU HARI NANTI" - Ningsih, Yulia; Ahmadi, Yusep; Nengsih, Wika (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2021)
Poetry is one type of literary work that contains figurative meanings, each set of words must of course use aesthetic words so that the expression of the array is interesting to present. In analyzing a poem, one must know the meaning of the poem. For this reason, the researcher uses Ingarden's Strata Norma analysis in analyzing a poem entitled "On One Day Later" by Sapardi Djoko Damono. The term norms according to Wellek and Warren are not simple or romantic and moral or policy norms. But it needs to be understood as an absolute rule that is excluded from the experience of reading a work. The formulation of the problem in this research is how is the norm strata of poetry entitled "On a Day Later"? With the aim of describing the layers of norm strata contained in the poem. The method used in this research is descriptive qualitative by analyzing an object of poetry and then the results are outlined in the form of a series of words. The results of the analysis of the poem have layers of meaning, which in essence, the poem has a deep classical meaning, from the title "On a Day Later" can be interpreted as "something that will happen in the future" or "death" that befell my figure in the poem. It is said by the object of a writer that "I" will not let the figure of "You" a reader be lonely without his presence when that day arrives. So that the figure "I" pours out the verses in the poetry that always accompany the figure of "You".